Autism-like phenotype across the lifespan of Shank3B-mutant mice of both sexes - Jakub Szabó; Johan Filo; Rebeka Démuthová; Emese Renczés; Veronika Borbélyová; Daniela Ostatníková; Peter Celec (Journal of Neurodevelopmental Disorders)
Abstract Background High heritability (80–90%) of the autism spectrum disorder (ASD) and sex-biased incidence (3–4 times more boys than girls) suggest the roles of genetic predisposition and sex in the etiopathogenesis of the disorder. As ASD is commonly diagnosed in early childhood, most of the research is focused on children, yet animal research predominantly uses adult-aged animals. The effect of aging on the core and secondary ASD symptomatology is understudied, both in patients and animal models of ASD. Methods To investigate the effect of aging on sociability, repetitive behavior, exploration, locomotor activity, anxiety-like behavior, and object-avoidance behavior, behavioral phenotyping was conducted in Shank3B −/− (n = 67) and C57BL/6J wild-type (WT, n = 68) mice of both sexes (female n = 70, male n = 65) in adolescence (1–2 months of age, n = 42), adulthood (3–6 months of age, n = 40), and old age (12–18 months of age, n = 53). Results Social deficits were observed only in old Shank3B −/− males. Anxiety-like behavior peaked in adulthood with Shank3B −/− mice roughly 20% more anxious than controls. Repetitive grooming and object-induced avoidance behavior were twice more prevalent in Shank3B −/− mice consistently across the lifespan. Hypoactivity (20% less distance moved) and reduced exploration (30% less rearing behavior) were recorded in Shank3B −/− mice and were more prevalent in female animals (30% less rearing behavior). Data were analyzed using the Three-way ANOVA (genotype, sex, age), followed by a posthoc Bonferroni correction to compare respective subgroups. Conclusions Present study shows that aging affects ASD-like phenotype in the Shank3B-mutant mouse model, even though the effect size seems to be small. The mechanisms underlying these partially sex-specific effects should be the subject of further research with potential translational implications.